Evaluating the cost and clinical effectiveness of long-acting, injectable aripiprazole and paliperidone palmitate once a month in a real-world setting [Corrigendum] - Hodgson RE (Dove Medical Press, 2019)
Hodgson RE. Clinicoecon Outcomes Res. 2019;11:517–524.On page 523, “Acknowledgments” and “Disclosure” sections should read as follows:AcknowledgmentsThe author would like to thank C Aladakatti, B Davenport, and T Saravanappa for their assistance with data collection and A Kinmond for help with manuscript revision. Dr Hodgson has received lecture fees and educational support from Janssen, Lundbeck and Otsuka. Lundbeck has provided financial support for medical writing assistance provided by David Whitford and HAVAS Just. Lundbeck had no influence or input in this service evaluation and submission of manuscript. DisclosureThe author reports no conflicts of interest in this work.Following a review of the funding statement in the “Acknowledgments” section post-publication, "unrestricted educational grant” was mistakenly used. The author apologies for this oversight.   Read the original article